2018
DOI: 10.1016/j.ceb.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalisation of RAC1 signalling

Abstract: RAC1 signalling has been implicated in a variety of dynamic cell biological processes that are orchestrated through regulated localisation and activation of RAC1. As a small GTPase, RAC1 switches between active and inactive states at various subcellular locations that include the plasma membrane, nucleus and mitochondria. Once activated, RAC1 interacts with a range of effectors that then mediate various biological functions. RAC1 is regulated by a large number of proteins that can promote its recruitment, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 68 publications
3
59
0
Order By: Relevance
“…Finally, we showed that the localization of Rac1 protein is at the leading edge of PC3 cells overexpressing Rac1 WT (in EGF‐stimulated cells) and Rac1 constitutively active (Figure 6C). These findings confirm that Rac1 needs to be bound to GTP, to be translocalized to the leading edge of migrating cells 38 . Thus, higher Rac1 activity in Rac1WT and Rac1Q61L cells caused Rac1 to localize at the leading edge, which in turn caused an increase in cell migration.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Finally, we showed that the localization of Rac1 protein is at the leading edge of PC3 cells overexpressing Rac1 WT (in EGF‐stimulated cells) and Rac1 constitutively active (Figure 6C). These findings confirm that Rac1 needs to be bound to GTP, to be translocalized to the leading edge of migrating cells 38 . Thus, higher Rac1 activity in Rac1WT and Rac1Q61L cells caused Rac1 to localize at the leading edge, which in turn caused an increase in cell migration.…”
Section: Discussionsupporting
confidence: 70%
“…These findings confirm that Rac1 needs to be bound to GTP, to be translocalized to the leading edge of migrating cells. 38 Thus, higher Rac1 activity in Rac1WT and Rac1Q61L cells caused Rac1 to localize at the leading edge, which in turn caused an increase in cell migration.…”
mentioning
confidence: 97%
“…Finally, we highlight proteins from our screen that interact with Rac1 Q61L and Rac1 P29S/ Q61L at specific regions within the cell ( Figure 2D). This follows recent literature showing diverse functions for Rac1 activity throughout the cell [37].…”
Section: Proteins That Bind Specifically To Active Rac1supporting
confidence: 87%
“…This implies that the nuclear and cytoplasmic localisations may influence the conformation of SWAP70, which resides in both compartments [41]. Although we have not followed up this observation, it is potentially related to the recognised differential regulation of RAC1 In the nucleus [42]. The enrichment of F-actin, PIP 3 and active RAC1 has previously been observed at the leading edge of adherent cells during their directed migration [24,[43][44][45].…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, we do not interpret this and the lack of impact of the R230C phosphoinositide binding mutation to mean that PI3K is not involved in the conformational activation of SWAP70. Although we have not followed up this observation, it is potentially related to the recognised differential regulation of RAC1 In the nucleus [42]. We also suggest that the high-FRET subpopulation of SWAP70 revealed within these cells is likely to be the active, functionally significant pool capable of activating RAC1 and perhaps other GTPases.…”
Section: Discussionmentioning
confidence: 84%